(De-)Thematisierung von Geschlecht Rekonstruktionen bei Studierenden der Erziehungs- und Bildungswissenschaften - Klinger, Sabine (Verlag Barbara Budrich, 2014)
How is "gender" received by students of educational research, pedagogy and related fields? What are the students' views on gender issues? Based on the observation that interest in gender issues is perceived more as an individual and somewhat anachronistic phenomenon, the empirical study reconstructs the influence of the educational institution university and the study of the specific subject area on students.